2020
DOI: 10.2174/1871520619666191014153554
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Anticancer, and Antibacterial Activity of Betulinic and Betulonic Acid C-28-Triphenylphosphonium Conjugates with Variable Alkyl Linker Length

Abstract: Background: Conjugation of triterpenoids such as betulinic acid 1 with the Triphenylphosphonium (TPP) group is a powerful approach to generating medicinal compounds. Their development proposes structure optimization in respect of availability and activity towards target cells and organelles. Selection of 1 or its precursor betulonic acid 2 and the optimal linker is of particular importance for drug candidate identification among the TPP-triterpenoid conjugates. Objective: In this study, new C-28-TPP conjugat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 63 publications
1
26
0
Order By: Relevance
“…It should be noted that antiproliferative activity was also detected in TPP and Cn-TPP itself, which seems to be related to the depolarization of the mitochondrial membrane potential [ 27 , 28 , 29 , 30 ]. In this regard, we consider these data on the use of CAM-Cn-TPP derivatives as one of the possible approaches to anti-cancer therapy, requiring more careful study and titration of concentrations and doses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that antiproliferative activity was also detected in TPP and Cn-TPP itself, which seems to be related to the depolarization of the mitochondrial membrane potential [ 27 , 28 , 29 , 30 ]. In this regard, we consider these data on the use of CAM-Cn-TPP derivatives as one of the possible approaches to anti-cancer therapy, requiring more careful study and titration of concentrations and doses.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that along with their antibacterial properties, TPP derivatives of various structures exhibit antiproliferative effects [27][28][29][30]. Most cancer cells possess functional mitochondria, but the oncogenic transformation itself often increases mitochondrial metabolism [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of a derivative of compound 17 with a mitochondrial targeting tag at C-28 would promote the opening of the mitochondrial permeability transition pore, increasing apoptosis. 55 The general triphenylphosphonium cation moiety was strategically synthesized in two steps from compound 17 . Briefly, compound 17 was treated with base, and the α,ω-dibromo alkane in DMF, the resultant product, was purified and treated with excess triphenylphosphine to yield the triphenylphosphonium (TPP) conjugate, compound 17a ( Figure 7 ).…”
Section: Triterpenoid Chemical Probesmentioning
confidence: 99%
“… 11 Coincidentally, C-28-TPP conjugated derivatives of betulinic acid with the alkyl/alkoxyalkyl linkers of variable length were up to 10–17 times more active against MCF-7 than for human skin fibroblasts. 12 …”
Section: Introductionmentioning
confidence: 99%